2014
DOI: 10.1128/aac.02284-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Cellular Vacuolar ATPase Impairs Human Papillomavirus Uncoating and Infection

Abstract: e Several viruses, including human papillomaviruses, depend on endosomal acidification for successful infection. Hence, the multisubunit enzyme vacuolar ATPase (V-ATPase), which is mainly responsible for endosome acidification in the cell, represents an attractive target for antiviral strategies. In the present study, we show that V-ATPase is required for human papillomavirus (HPV) infection and that uncoating/disassembly but not endocytosis is affected by V-ATPase inhibition. The infection inhibitory potencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…7F). This antibody binds to an epitope revealed only after disassembly in acidified endosomes (27,38). Control or OBSL1 siRNA-transfected cells were exposed to HPV16 PsV for 7 h. Control cells showed a high degree of 33L1-7 staining, whereas the L1-7 signal was strongly decreased, to 32%, in OBSL1 knockdown cells, further supporting the data showing that OBSL1 is required for HPV16 endocytosis.…”
Section: Hpv16 L2 Forms a Complex With Obsl1supporting
confidence: 65%
See 1 more Smart Citation
“…7F). This antibody binds to an epitope revealed only after disassembly in acidified endosomes (27,38). Control or OBSL1 siRNA-transfected cells were exposed to HPV16 PsV for 7 h. Control cells showed a high degree of 33L1-7 staining, whereas the L1-7 signal was strongly decreased, to 32%, in OBSL1 knockdown cells, further supporting the data showing that OBSL1 is required for HPV16 endocytosis.…”
Section: Hpv16 L2 Forms a Complex With Obsl1supporting
confidence: 65%
“…Following internalization, viral particles are found in CD63-positive endosomes recruiting syntenin-1, a CD63-interacting adaptor protein (35). The CD63-syntenin-1 complex was identified as a regulatory component in postendocytic HPV trafficking to multivesicular endosomes (35), where vacuolar ATPase and cyclophilins facilitate capsid disassembly and dissociation of L1 and L2 (36)(37)(38). DiGiuseppe and coworkers revealed that L2 amino acid residues 64 to 81 and 163 to 170 and the L2 C-terminal exposure on the cytosolic side of intracellular membranes enable interaction with cytosolic host cell factors (39).…”
mentioning
confidence: 99%
“…After internalization, the virus traffics through the endosomal system, requiring interactions with sorting nexin 17 in the endosome as well as the retromer complex and ␥-secretase in the trans-Golgi network (21)(22)(23)(24)(25)(26)(27). During this process, acidification and further conformational changes induced by CyPB result in L1 and L2 dissociation and viral uncoating (28,29). L2 then interacts with and permeabilizes the host cell membrane, actions that are dependent upon prior furin cleavage at the cell surface (30,31).…”
mentioning
confidence: 99%
“…Internalized virions enter the endosomal pathway, where acidification due to the V-ATPase proton pump triggers L1 uncoating (18) and the L2/vDNA complex separates from the dissociated L1 capsid and retrograde traffics to the trans-Golgi network (TGN) in a furin-, cyclophilin-, ␥-secretase-, and retromer-dependent manner (19)(20)(21)(22)(23)(24). Transport of L2/vDNA to the TGN is essential, and prolonged residence in the endosomal compartment may be detrimental, as the acid-dependent cathepsins B and L restrict infection (25).…”
mentioning
confidence: 99%